2006
DOI: 10.1177/039139880602901206
|View full text |Cite
|
Sign up to set email alerts
|

CFD Simulation of a Novel Bileaflet Mechanical Heart Valve Prosthesis - An Estimation of the Venturi Passage Formed by the Leaflets

Abstract: The aim of this study was to validate the flow characteristics of the novel Helmholtz-Institute Aachen Bileaflet (HIA-BL) heart valve prosthesis. The curved leaflets of the HIA-BL valve form a Venturi passage between the leaflets at peak systole. By narrowing the cross section the flow accelerates and the static pressure at the central passage decreases according to the Venturi effect. The low-pressure zone between the leaflets is expected to stabilize the leaflets in fully open position at peak systole. To in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…In other studies, only part of the cycle is considered (Myers & Porter 2003) and the numerical simulation imposes symmetries (Cheng, Lai & Chandran 2004) so as to decrease the computational cost. In addition, in the majority of the literature, turbulence models are used to avoid the explicit simulation of the smallest scales (Grigioni et al 2005;Yokoyama et al 2006;Alemu & Bluestein 2007, among many others); this substantially reduces the nodes of the mesh and allows for larger integration time steps, but at the expense of the information on the turbulence fine scales whose accurate description is mandatory for the comprehension of the clinical phenomena mentioned above. Recently, Borazjani et al (2007) and Borazjani, Ge & Sotiropulos (2008) considered the full three-dimensional flow dynamics in an axisymmetric aortic root, including fluid-structure interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, only part of the cycle is considered (Myers & Porter 2003) and the numerical simulation imposes symmetries (Cheng, Lai & Chandran 2004) so as to decrease the computational cost. In addition, in the majority of the literature, turbulence models are used to avoid the explicit simulation of the smallest scales (Grigioni et al 2005;Yokoyama et al 2006;Alemu & Bluestein 2007, among many others); this substantially reduces the nodes of the mesh and allows for larger integration time steps, but at the expense of the information on the turbulence fine scales whose accurate description is mandatory for the comprehension of the clinical phenomena mentioned above. Recently, Borazjani et al (2007) and Borazjani, Ge & Sotiropulos (2008) considered the full three-dimensional flow dynamics in an axisymmetric aortic root, including fluid-structure interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In this research framework, Grigioni et al (2005a) performed a numerical simulation on a model of mechanical valve placed in a physiological aortic root shaped model, furnishing indications about the role of Valsava sinus on the fluid dynamic downstream of the valve at mid systole. Yokoyama et al (2006) demonstrated that curved leaflet configuration generates a Venturi effect that is able to reduce the boundary layer separation zones and stabilize the leaflets' position. Ge et al (2003) provided an insight into the complex hemodynamics of a bileaflet MHV at the maximum Reynolds number, putting in evidence that high grid densities are mandatory, in order to fully characterize local aspects of the flow field downstream of the prosthetic valve.…”
Section: Introductionmentioning
confidence: 99%
“…This region is distinct as far as 2 diameters from the valve but shows a much smaller fluid speed than the principal flow. Some fluid speeds were zero velocities and some were of negative values as seen in figure [5]. The negative velocities oppose the flow direction, some of which appeared upstream of the valve.…”
Section: Resultsmentioning
confidence: 93%
“…At the opened leaflet, the fluid jet carries turbulent velocity fluctuations further downstream than in configuration I. The region of lower counter flow velocities which is in-between the high turbulent diffusivities that resulted from jet velocities is bounded by regions of high shear [5]. This recirculation phenomenon has been known to have a physiological impact.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation